MEDIA PEMBELAJARAN MICROLEARNING DENGAN PENDEKATAN PROBLEM BASED LEARNING PADA MUATAN IPAS MATERI KERAGAMAN BUDAYA LOKAL - Sugiarti, Iis Yeni; Putri, Dian Permana; Mudopar; Dwiniasih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Iconic Cirebon is a city of culture and the city of guardians has a lot of cultural heritage from mentifact, sosifact, and artifacts. One form of culture, artifacts, can be used as a relevant learning resource to get to know Cirebon's local wisdom. Unfortunately, this cultural heritage has not been applied optimally in the learning process. So students do not understand well the variety of local culture of Cirebon. The purpose of this study was to develop and analyze the validity of microlearning learning media with a problem-based learning approach to the content of IPAS local cultural diversity material. The research method used is RnD with the development model used at the analysis, design, and development stages. Data collection techniques include observation, interviews, and documentation while validity data analysis techniques use media and material feasibility tests. Media validation obtained 83.75% while material validation obtained 82.5% which shows the presentation of Cirebon Mask using microlearning with a PBL approach can increase understanding of local culture contextually, meaningful learning innovations, and foster 21st century skills.